Transmission of climate shocks to livestock prices in regulated and unregulated markets: Evidence for raw milk in Colombian tropical livestock - Andres Mauricio Vargas Pérez; José Luis Ramos Ruiz; Sadan Alexander De la Cruz Almanza (Economía Agraria y Recursos Naturales)
This research investigates the impact of climate variability on the price trend of raw milk in Colombia, which is traded in regulated and unregulated markets. The findings indicate that climate variations do not affect the regulated price, whereas the unregulated market shows an asymmetric price response. The price increase is more significant than a favorable event in an adverse shock, such as a drought. This may clarify why small-scale producers tend to favor this market despite receiving lower prices on average for their raw milk.